The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1002/aoc.1130
|View full text |Cite
|
Sign up to set email alerts
|

Efficient palladium–ferrocenylphosphine catalytic systems for allylic amination of monoterpene derivatives

Abstract: Ferrocenylphosphines added to [Pd(µ-Cl)(η 3 -C 3 H 5 )] 2 dimeric precursor produce efficient catalysts to effect the allylic amination of terpenic allylacetates. Particularly convenient are tetrakis(diphenylphosphino)ferrocene and 1,1 -bis(diphenylphosphino)ferrocene, which allow the amination of allylacetates with good to excellent selectivity, and have turnover numbers as high as 80 000, for instance, for the formation of allylaniline. Herein, we report on reactions that selectively transform geranylacetate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
0
11
1
Order By: Relevance
“…The result obtained with geranyl acetate 5 was less efficient than the one reported by Nguyen et al [18] using palladium-ferrocenylphosphine catalytic systems. it is noteworthy that all amines derived from optically active perillyl acetate 3 exhibit optical activity.…”
Section: Amination Of Allylic Terpenic Acetatescontrasting
confidence: 60%
See 2 more Smart Citations
“…The result obtained with geranyl acetate 5 was less efficient than the one reported by Nguyen et al [18] using palladium-ferrocenylphosphine catalytic systems. it is noteworthy that all amines derived from optically active perillyl acetate 3 exhibit optical activity.…”
Section: Amination Of Allylic Terpenic Acetatescontrasting
confidence: 60%
“…Recently, Nguyen et al have reported efficient palladium catalytic systems for the allylic amination of monoterpenic acetates [18]. The catalytic systems combining a Pd(ii) precursor and a ferrocenylphosphine ligand shows an excellent selectivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other methods to prepare these amines start on the corresponding acetates and are generated via allylic amination catalyzed by palladium complexes. [157][158][159][160] Because hydroamination occurs with 100 % atom efficiency, meaning all substrate molecules can be found in the product, plenty of investigations to add diethylamine in one step to myrcene have been described (Table 6). 1082 www.chemsuschem.org…”
Section: Routes To Aminesmentioning
confidence: 99%
“…The same amines can be obtained via the allylic amination of the corresponding acetates. [35][36][37][38] Nevertheless, the direct hydroamination of myrcene is proven to be the better route because the acetates are rarely available. If the pathway is telomerisation, the so-called tail-to-tail telomer (tttelomer, 3) is mainly generated.…”
Section: Hydroamination Under Single Phase Conditionsmentioning
confidence: 99%